Hubungan Pengetahuan dan Sikap dengan Perilaku Higiene Sanitasi Penjamah Makanan pada Food Court Baseball UNESA Ketintang - Engga Reni Setyaningrum; Rahayu Dewi Soeyono (Jurnal Ilmu Kesehatan dan Gizi, 2025)
The Baseball Food Court is one of the facilities provided by Surabaya State University to meet the food needs of campus residents at Surabaya Ketintang State University. Food contamination can occur in the Food Court environment if food is not processed properly and in accordance with food sanitation hygiene guidelines and can threaten public health. This research aims to determine the relationship between knowledge and attitudes and the sanitation hygiene behavior of food handlers at the UNESA Ketintang Baseball Food Court. This research is a quantitative study with a cross sectional design with a sample size of 20 people. The respondents in this study were food handlers at the UNESA Ketintang Baseball Food Court. The data analysis used in this research was the Chi Square Test. The results of this study show that there is a relationship between knowledge and behavior of food handlers with a p-value of 0.001 and there is a relationship between attitudes and behavior of food handlers with a p-value of 0.007. The conclusion of this research is that food handlers at the UNESA Ketintang Baseball Food Court already have good sanitation knowledge, attitudes and hygiene behavior. So it is recommended that food handlers at the UNESA Ketintang Baseball Food Court continue to maintain and be able to improve their knowledge, attitudes and food sanitation hygiene behavior so that they remain in a good category.